Down‐regulation of microRNAs of the miR‐200 family and up‐regulation of Snail and Slug in inflammatory bowel diseases — hallmark of epithelial−mesenchymal transition. Issue 10 (26th April 2016) - Zidar, Nina; Boštjančič, Emanuela; Jerala, Miha; Kojc, Nika; Drobne, David; Štabuc, Borut; Glavač, Damjan
Abstract: Fibrosis is an important feature of inflammatory bowel diseases (IBD), particularly Crohn's disease (CD), but its pathogenesis is poorly understood. To determine the postulated involvement of epithelial−mesenchymal transition (EMT) in the development of fibrosis in IBD, we analysed the expression profiles of the miR‐200 family which has been shown to induce EMT in experimental models and various human diseases. We also analysed the expression of Snail and Slug, postulated targets of the investigated microRNAs. Ten patients with ulcerative colitis (UC) and 10 patients with CD who underwent colon resection were included. From each, two tissue samples were chosen (one with the most severely and one with the least affected or normal mucosa) for analysis of microRNAs expression using real‐time polymerase chain reaction, and Snail and Slug expression using immunohistochemistry. We found significant down‐regulation of all investigated microRNAs in CD, and of three investigated microRNAs in UC, in comparison to the normal or the least affected mucosa. Comparing UC and CD, four microRNAs were significantly more down‐regulated in CD than in UC. Snail and Slug were expressed in the injured epithelium and occasionally in mesothelial cells and submesothelial fibroblasts. Our finding of down‐regulation of the miR‐200 family and up‐regulation of transcription repressors Snail and Slug supports the postulated role of EMT in the pathogenesis of fibrosis in IBD. The described expression patterns are consistent with the notion that fibrosis does not occur only in CD but also in UC, being much more severe in CD.